Antibacterial Potential of Ethanol Extract from White Pidada (Sonneratia alba) Leaves Against Gastrointestinal Pathogens - Rudiah, Sukhriatun (Journal Microbiology Science, 2024)
The antibacterial properties of the ethanol extract of White Pidada leaves (Sonneratia alba), a mangrove plant rich in bioactive compounds such as phenols, flavonoids, steroids, saponins, triterpenoids, tannins, and alkaloids, were evaluated in this study. The research focused on determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) against gastrointestinal infection-causing bacteria, including Salmonella typhii, Shigella dysenteriae, Escherichia coli, and Vibrio cholerae. The MIC results showed effective inhibition at concentrations as low as 0.025% for Shigella dysenteriae, 0.05% for Salmonella typhii and Vibrio cholerae, and 0.5% for Escherichia coli. The MBC analysis indicated bactericidal activity at higher concentrations, with significant effects observed at 1% for Salmonella typhii, 0.05% for Shigella dysenteriae and Vibrio cholerae, and 0.1% for Escherichia coli. Agar diffusion tests confirmed that increasing extract concentrations correlated positively with the inhibition zone diameter, highlighting the potential of White Pidada leaves as a natural antibacterial agent.